Predisposition Factor of Safety of Landslide Dams from Typhoon Talas, Kii Peninsula, Japan - Daikai Rikuto; Gomez Christopher; Balazs Bradak; Aditya Saputra; Danang Sri Hadmoko (Universitas Muhammadiyah Surakarta, 2022)
Landslide dams are less frequent than other landslides, and their very existence is often very-much short-lived, because the temporary dam tends to collapse rapidly. Because of the resulting lack of evidences, there has been less research done on this topic, although the potential catastrophe they can be at the origin of needs assessment. For this purpose, the present contribution aims at differentiating landslides that trigger dams against those that do not inside a group of valleys of the Kii peninsula in Japan, where landslides occurred af-ter the typhoon Talas in 2011. Using topographic map before the event and LiDAR data in its aftermath, the authors have calculated the factor of safety (FS) of different landslides in the same valleys, comparing the da-ta of landslides that created dams against those that did not. The results show that landslides that triggered dams seemed to have a higher FS than those that did not. The authors suggest that it is because larger land-slides are needed and thus appear more stable, but also because at the location where the slopes are stable, the riverbed can incise further instead of growing horizontally, and thus the sediments damming the channel have more chances to block it (as it is narrow) and stop the river from flowing.